2021
DOI: 10.1002/cam4.4129
|View full text |Cite
|
Sign up to set email alerts
|

SphK1‐driven autophagy potentiates focal adhesion paxillin‐mediated metastasis in colorectal cancer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Earlier, a study showed SphK1 modulated EMT markers in CRC and its inhibition reduced cancer cell migration ( 90 ). In support of this, a study published recently demonstrated that SphK1 stimulates autophagy in CRC cells and that autophagy driven by SphK1 may promote the invasion and metastasis of CRC by promoting the expression of focal adhesion paxillin ( 45 ). In another finding, CRC cells were protected from EMT by inhibiting autophagy.…”
Section: Role Of Autophagy In Emt and Metastasismentioning
confidence: 80%
“…Earlier, a study showed SphK1 modulated EMT markers in CRC and its inhibition reduced cancer cell migration ( 90 ). In support of this, a study published recently demonstrated that SphK1 stimulates autophagy in CRC cells and that autophagy driven by SphK1 may promote the invasion and metastasis of CRC by promoting the expression of focal adhesion paxillin ( 45 ). In another finding, CRC cells were protected from EMT by inhibiting autophagy.…”
Section: Role Of Autophagy In Emt and Metastasismentioning
confidence: 80%
“…Another recent study showed that UPR-induced autophagy driven by Sec62 increases the GC invasive ability [ 34 ]. Wu et al demonstrated that SphK1-induced autophagy enhances focal adhesion paxillin-mediated metastasis of CRC [ 35 ]. MST4 stimulates autophagy by phosphorylating ATG4B to promote the tumorigenicity of glioblastoma [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy critically has been reported affecting the carcinogenesis of CRC ( Huang et al, 2018 ; Gao et al, 2022 ). For example, Sphk1-driven autophagy enhanced CRC metastasis ( Wu et al, 2021 ). However, bivalent β-Carbolines induced autophagy to depressed CRC growth ( Zhang et al, 2021 ), which means autophagy played a balance role in the occurrence and death of tumors.…”
Section: Introductionmentioning
confidence: 99%